2012
DOI: 10.1093/cercor/bhs105
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cortical and Thalamic Excitability in Freely Moving APPswe/PS1dE9 Mice Modeling Epileptic Activity Associated with Alzheimer's Disease

Abstract: Amyloid precursor protein transgenic mice modeling Alzheimer's disease display frequent occurrence of seizures peaking at an age when amyloid plaques start to form in the cortex and hippocampus. We tested the hypothesis that numerous reported interactions of amyloid-β with cell surface molecules result in altered excitation-inhibition balance in brain-wide neural networks, eventually leading to epileptogenesis. We examined electroencephalograms (EEGs) and auditory-evoked potentials (AEPs) in freely moving 4-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 71 publications
9
73
1
Order By: Relevance
“…Due to the long-term experimental character and experimental time schedules (see the following), females could not be recorded within the same stage of the estrous cycle. In addition, the stages of the estrous cycle were reported not to influence basic EEG related parameters [31]. All experimental mice were housed in groups of 3-4 in clear Makrolon cages type II with ad libitum access to drinking water and standard food pellets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the long-term experimental character and experimental time schedules (see the following), females could not be recorded within the same stage of the estrous cycle. In addition, the stages of the estrous cycle were reported not to influence basic EEG related parameters [31]. All experimental mice were housed in groups of 3-4 in clear Makrolon cages type II with ad libitum access to drinking water and standard food pellets.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have analyzed selective electrical activity and individual frequency characteristics from electrocorticograms and other deflections including sleep studies in APP transgenic mice [4, 22, 26, 2931]. In contrast to these studies, we present a systematic FFT based frequency analysis and multiparameter longitudinal seizure evaluation from both cortical M1 and hippocampal CA1 recordings in APPswePS1dE9 and controls based on nonrestraining EEG radiotelemetry.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in transgenic mouse models of AD, information processing deficits are associated with an altered excitation-inhibition balance in brain-wide neuronal networks. For instance, transgenic mice carrying human APPswe and PS1-A264E transgenes show impaired auditory gating, which is associated with the overproduction of Abeta42 [124], while APPswe/PS1dE9 APdE9 mice display aberrant AEP as reflected by larger cortical and thalamic amplitudes of different AEP components to both S1 and S2 stimuli with a paired stimulus index, indicating that the earliest cortical component N1 was less suppressed in AD-modeled mice than in wild-type animals [125]. …”
Section: Pharmaco-event-related Potentialsmentioning
confidence: 99%
“…Other studies in AD mouse models have indicated that the thalamus is directly engaged during certain seizures (Gurevicius, et al, 2013). These lines of evidence suggest that the corticothalamic network may be dysfunctional in AD.…”
Section: Introductionmentioning
confidence: 99%
“…However, seizures and epileptiform activity in AD may be vastly underestimated due to subclinical epileptiform activity and non-convulsive seizures (Vossel, et al, 2013). Multiple mouse models of AD also exhibit a wide range of network dysfunction manifested as generalized epileptic discharges and spontaneous convulsive and non-convulsive seizures (Corbett, et al, 2013,Gurevicius, et al, 2013,Harris, et al, 2010,Hazra, et al, 2013,Lalonde, et al, 2005,Minkeviciene, et al, 2009,Palop, et al, 2007,Verret, et al, 2012,Vogt, et al, 2011). However, the precise mechanisms by which seizures arise in AD and develop into dysfunctional networks that incorporate a wide range of brain regions is unknown.…”
Section: Introductionmentioning
confidence: 99%